The Less Well-Known Little Brothers: The SLC9B/NHA Sodium Proton Exchanger Subfamily—Structure, Function, Regulation and Potential Drug-Target Approaches - Anderegg, Manuel A.; Gyimesi, Gergely; Ho, Tin Manh; Hediger, Matthias A.; Fuster, Daniel G. (Frontiers in Physiology, 2022)
The SLC9 gene family encodes Na+/H+ exchangers (NHEs), a group of membrane transport proteins critically involved in the regulation of cytoplasmic and organellar pH, cell volume, as well as systemic acid-base and volume homeostasis. NHEs of the SLC9A subfamily (NHE 1-9) are well-known for their roles in human physiology and disease. Much less is known about the two members of the SLC9B subfamily, NHA1 and NHA2, which share higher similarity to prokaryotic NHEs than the SLC9A paralogs. NHA2 (also known as SLC9B2) is ubiquitously expressed and has recently been shown to participate in renal blood pressure and electrolyte regulation, insulin secretion and systemic glucose homeostasis. In addition, NHA2 has been proposed to contribute to the pathogenesis of polycystic kidney disease, the most common inherited kidney disease in humans. NHA1 (also known as SLC9B1) is mainly expressed in testis and is important for sperm motility and thus male fertility, but has not been associated with human disease thus far. In this review, we present a summary of the structure, function and regulation of expression of the SLC9B subfamily members, focusing primarily on the better-studied SLC9B paralog, NHA2. Furthermore, we will review the potential of the SLC9B subfamily as drug targets.